An Act for the Punishing of Criminal Offenders, 1771 N. H. Acts and Laws ch. 6, §5, p. 17 - (:unkn) unknown (General Publisher, 1771)
Prohibited going "armed offensively."
--
Keywords: CARRY - INTENT TO COMMIT CRIME